Estrategias didácticas para la estimulación cognitiva en niños de Inicial II - Iñiguez Tipan, Allisson Viviana (2023)
Given the constant changes in education, the need to have interactive communication and to generate learning processes that respond to the dimension of cognition is revealed. For this reason, the present investigation starts from the need that is observed in pre-professional practices, with the objective of analyzing the didactic strategies and their influence on the cognitive stimulation of the students of Initial II children of the Miraflores Educational Unit. We worked with essences of a methodology with a mixed and field approach. To obtain information, it was considered to observe the children through a checklist. Likewise, an observation guide was applied to teachers, accompanied by a survey, to learn about the implementation of didactic strategies in the development of activities that consider cognitive stimulation. In addition, from an interview with the psychologist and a test of basic functions focused on the cognitive abilities of the students, where difficulties were found in the areas of cognition. The results obtained allowed the analysis and interpretation to be elaborated, from which the conclusion is obtained that the didactic strategies must be contemplated in the teaching task through dynamic, playful and attractive activities that favor learning while cognitively stimulating children.